CASE STUDY OF CORPORATE SOCIAL RESPONSIBILITY PRACTICES OF STATE BANK OF INDIA - Barad, Manisha M. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Corporate Social Responsibility is the term with present century lives, this paper contains the various aspects of CSR policy followed by State bank of India. this study presents CSR practices of State bank of India, secondary source of data has been used for the study. The present study describes fund allocation and analysis of sector wise CSR spending. SBI foundation also plays important role in SBI corporate social responsibility practices.